EKOKRITIKISME KOREOGRAFI SATU MILIAR TOKEK KARYA AYU TITIS RUKMANA SARI - Dewi Wulansari; Tubagus Mulyadi (Institut Seni Indonesia Surakarta, 2021)
Satu Miliar Tokek by Ayu Titis Rukmana Sari, was inspired by the phenomenon of the Kedung Monggo community towards the price of a billion geckos. This phenomenon has an impact on the burning of the banyan tree where the gecko resides. This research has the problem of how to choreograph one billion geckos and how to ecocriticism in the work of one billion geckos. To answer the problem of choreography, Slamet Md's concept of dance formation consists of motion, rhythm, expression, or feeling, costumes, stage, and dancers. To explore ecocriticism, the opinion of F.X. Widaryanto. The manifestation of eco-criticism in performing arts products of past creative traditions is heavily influenced by natural phenomena. This shows that the works of art in the past gave direction to the audience to protect the environment. The method used in this research is a qualitative research method with a choreographic approach. The results of this study indicate that the work of one billion geckos is a work of art as a form of social criticism, especially in the Kedung Monggo community, which is manifested in the flow of dance choreography.Keywords: Satu Miliar Tokek, Choreography, and Ecocriticism